IDENTIFICATION AND PLANNING OF POVERTY AREAS IN PALEMBANG CITY - Bastiar Tambuh; Novita Wulandari; Fitri Herdayani; Ardiansyah Amri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to identify, describe and analyze the Poverty Area Mapping of Palembang City. This study uses a descriptive qualitative approach with explanatory research type, with the number of informants as many as 100 people determined randomly. Data collection techniques in this study were using documentation, observation, questionnaires, interviews, and literature study.The results of the study prove that (1) There has been uneven and inappropriate assistance provided by the Government/Regional Government (Province, Regency/City) in poverty alleviation in Palembang City; (2) Unavailability of up to date data regarding the number of poor people in Palembang City; (3) Poverty Alleviation Programs that are under the regional structure and characteristics of the people of Palembang City, namely programs that are oriented or based on human resource development; (4) The need for a pilot project focused on as a pilot program for poverty alleviation that is oriented to human resource development. Keywords: Identification, Planning, and Poverty